The effect of gargling with 10% concentration of green betel leaf (Piper betle L.) decoction on gingivitis in pregnant women - Firmansyah, Yanuar; Hidayati, Sri; Ulfah, Siti Fitria (Indonesian Journal of Dental Medicine, 2025)
Background:  In pregnant women, gingivitis can result from hormonal fluctuations, local oral conditions, and behavioural factors. Bacteria and inflammatory mediators may enter the circulation and reach the uterus, which can increase the risk of low birth weight and preterm delivery. The decoction of green betel leaves exhibits antibacterial properties that may help prevent gingivitis. Purpose: This study addresses the high prevalence of gingivitis among pregnant women at Unit Pelayanan Terpadu (UPT) Pusat Kesehatan Masyarakat (Puskesmas) / Health Centre Kamal. It aims to evaluate the effects of gargling a 10% green betel leaf decoction on gingivitis in pregnant women at UPT Puskesmas Kamal, Bangkalan District. Methods: This study employed a quasi-experimental design, involving 83 pregnant women as respondents. The gingival index, as proposed by Loe and Silness, was measured both before and after gargling to assess the impact of the intervention. Additionally, an observation sheet was utilised to evaluate participants’ adherence to the gargling regimen at home. Data were analysed using the Wilcoxon test. Results: The results indicated an improvement in the average initial gingival index from 2.1013, classified as severe, to 1.2787, classified as moderate. The Wilcoxon test yielded a significance value of p<0.05, demonstrating a statistically significant effect of gargling a 10% green betel leaf (Piper betle L.) decoction on gingivitis in pregnant women at UPT Puskesmas Kamal, Bangkalan District. Conclusion:  Betel leaf (Piper betle L.) can reduce the prevalence of gingivitis in pregnant women.